Antecedentes contextuais dos comportamentos de cidadania organizacional - Andrade, Taís de (2017)
Organizational Citizenship Behavior has been considered vital for the functioning of organizations, since this behavior denotes the spontaneous cooperation of individuals and their involvement with activities, in addition to those prescribed for the execution of their formal role. Thus, the general objective of this study was to propose and apply a framework for the analysis of Organizational Citizenship Behaviors, composed of contextual antecedents associated to Interpersonal Trust, Organizational Trust and Organizational Support, aiming to establish interactions between them. For that, a descriptive research of the type survey was carried out, using quantitative methodologies for the survey and analysis of the results. The translation, the cross-cultural adaptation and validation of the scale of Organizational Citizenship Behaviors for Knowledge Workers and the measure of Interpersonal Trust in the national context were initially carried out. After these steps, a pilot study was carried out with the application of these questionnaires to 247 workers from the private educational sector. The second stage of the study consisted in the application of the survey to 988 workers of the educational sector belonging to thirteen private educational organizations. The obtained data were analyzed with the support of the software SPSS and AMOS, through the Modeling of Structural Equations (MSE). The main results show the relationship of influence of the contextual antecedents on the Organizational Citizenship Behaviors for Knowledge Workers, and all the constructs had a positive and significant influence on the OCB. Among the contextual antecedents, the one that most affected the OCB was Interpersonal Confidence. The hypotheses defined from the theoretical arguments presented were, for the most part, confirmed. Also, by confirming the influence of the contextual antecedents on Organizational Citizenship Behavior, the study allowed a new look at the OCB, considered an emerging theme in the studies on Organizational Behavior. The reflections that emerge from the findings of this research suggest that the social context, where interactions occur between individuals and between them and the organization, plays a central role in stimulating the behaviors of members in organizations.